Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ð¾Ð¹ ÐºÐ¾Ñ€Ð´Ð¾Ð²Ð¾Ð¹ ÐºÑ€Ð¾Ð²Ð¸ Ð½Ð° ÑÑ‚Ñ€ÑƒÐºÑ‚ÑƒÑ€Ñƒ Ð¸Ð¼Ð¼ÑƒÐ½Ð¾ÐºÐ¾Ð¼Ð¿ÐµÑ‚ÐµÐ½Ñ‚Ð½Ñ‹Ñ… Ð¸ Ð´Ñ€ÑƒÐ³Ð¸Ñ… Ð¶Ð¸Ð·Ð½ÐµÐ½Ð½Ð¾ Ð²Ð°Ð¶Ð½Ñ‹Ñ… Ð¾Ñ€Ð³Ð°Ð½Ð¾Ð² Ð¿Ñ€Ð¸ Ð¾ÑÑ‚Ñ€Ð¾Ð¼ Ð³Ð½Ð¾Ð¹Ð½Ð¾Ð¼ Ð¿ÐµÑ€Ð¸Ñ‚Ð¾Ð½Ð¸Ñ‚Ðµ - Goltsev, K. A.; Volina, V. V.; Kozhina, O. Yu.; Ostankov, M. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2011)
The experimental research of the effect of cryopreserved human cord blood (cHCB) introduction on the recovery of structure of immuno-competent and other vital organs of rats with acute pyoperitonitis (APP) was performed. It was shown the activation of regenerative processes under effect of cHCB in immune system organs as well as other ones (liver, kidneys, intestine and lungs) exposed to pathological changes at peritonitis development. The obtained results provide the reasons for probable cHCB administration as an immunomodulating therapy at development of acute pyoperitonitis in clinical practice.